Comparison of Methanol, Ethanol, or n-Butanol Blending with Unleaded Gasoline on Exhaust Emissions of an SI Engine - Varol, Y.; Oner, C.; Öztop, Hakan Fehmi; Altun, S. (Taylor & Francis Inc, 2014)
Air pollution is becoming a serious problem in many urban cities of the world and it can have a serious effect on both health and the environment. Although experimental studies have shown that alcohol fuels burn cleaner than unleaded gasoline and produce lesser emission, there is limited information regarding the comparison among the alcohol fuels as gasoline additive in spark-ignited engines. Therefore, a comparison has been performed in this experimental work on the exhaust emissions of a spark-ignited engine when operating on a blend of methanol, ethanol, or n-butanol with unleaded gasoline. Methanol, ethanol and n-butanol were added to unleaded gasoline by mass percent of 10% (denoted as M10, E10 and Bu10, respectively), and then tested in a four cylinder, four strokes spark-ignited engine. Although the experimental results show little differences in exhaust emissions between M10, E10, and Bu10, compared with Bu10, M10 and E10 have lower carbon monoxide emission and higher fuel consumption, hydrocarbon, and CO2 emission. Compared with unleaded gasoline, blended fuels containing different alcohols appear to have a lower carbon monoxide and hydrocarbon emissions and a higher fuel consumption rate and CO2 emissions.
Keywords: n-butanol; ethanol; exhaust emissions; methanol; spark-ignited engine